IMPLEMENTATION OF HEALTH EDUCATION USING AUDIO-VISUAL MEDIA ON PERINEAL WOUND CARE IN POSTPARTUM MOTHERS WITH KNOWLEDGE DEFICIT PROBLEMS IN THE ROSE ROOM RSI JEMURSARI SURABAYA - Reni Dwi Novita Wati; Nurul Kamariyah; R. Khairiyatul Afiyah; Nur Ainiyah (Nurse and Holistic Care)
Introduction: The problem that often occurs in postpartum mothers is the lack of knowledge of mothers in caring for perineal wounds.